The political economy of poverty, equity, and growth: a comparative study - Lal, D. Deepak Lal.; Myint, H. H. Myint (New York, Clarendom Press., 1996)
This wide-ranging and innovative book synthesises the findings of a major international study of the political economy of poverty, equity, and growth. It is based primarily on analytical economic histories of twenty-one developing countries from 1950 to 1985, but also takes into account of the much wider literature on the subject. It represents an ambitious interdisciplinary attempt to identify patterns in the interplay of initial conditions, institutions, interests, and ideas which can help to explain the different growth and poverty alleviation outcomes in the Third World.
Includes bibliography references and index